Rancang Bangun Sistem Keamanan Anak berbasis Modul GSM menggunakan Protokol HTTP - Hady Hermawan; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Security is a condition that is free from danger, danger word can be related to the form of crime , accident, and others. All peoples always trying to fulfill that condition, but there are some age who cant fulfill this condition. One of them is children safety, children tend to be careless than adults. This is due to an immature mindset and unstable emotions, therefore it triggers crimes againts children. So that it requires strict supervision by parents, on the other side the parents cant monitor their childs safety all the time because they tend to be busy with theis jobs. Seeing this problem, the author would like to recommend a solution in the form of IoT (Internet of Things) with the topic of child safety system GSM based module using HTTP protocol. IoT allows system to communicate or transfer data by themselves using IP connectivity. The System cant do full supervision, but this system able to provide information about location coordinates of their child when the child is in danger and pressing a push button on the system. This system uses a GSM module so it can directly access the webserver to transmit data that has been read by the GPS module and processed by Arduino Uno. The data that has been read will be sent to the webserver and then forwarded by the registered user. Based on the research results the GSM module has the best network strength value in outdoor conditions with value 22 (-69 dBm), the GPS module has data accuracy with an average difference value of 3,15 meters, Telegram chatbot has a perfect data accuracy value with 100% success rate without experiencing lost data.